Mass spectrometry imaging of surface lipids on intact Drosophila melanogaster flies. (17th February 2014) - Kaftan, Filip; Vrkoslav, Vladimír; Kynast, Philipp; Kulkarni, Purva; Böcker, Sebastian; Cvačka, Josef; Knaden, Markus; Svatoš, Aleš
<x xml:space="preserve">Abstract</x> The spatial distribution of neutral lipids and semiochemicals on the surface of six‐day‐old separately reared naive Drosophila melanogaster flies has been visualized and studied using matrix‐assisted laser desorption/ionization‐time of flight (MALDI‐TOF) mass spectrometry and laser‐assisted desorption/ionization (LDI)‐TOF imaging (MSI). Metal targets were designed for two‐dimensional MSI of the surface of 3‐D biological objects. Targets with either simple grooves or profiled holes designed to accurately accommodate the male and female bodies were fabricated. These grooves and especially holes ensured correct height fixation and spatial orientation of the flies on the targets after matrix application and sample drying. For LDI‐TOF to be used, the flies were arranged into holes and fixed to a plane of the target using fast‐setting glue. In MALDI‐TOF mode, the flies were fixed as above and sprayed with a lithium 2, 5‐dihydroxybenzoate matrix using up to 100 airbrush spray cycles. The scanning electron microscopy images revealed that the deposits of matrix were homogenous and the matrix formed mostly into the clusters of crystals (40–80 µm) that were separated from each other by an uncovered cuticle surface (30–40 µm). The MSI using target with profiled holes provided superior results to the targets with simple grooves, eliminating the ion suppression/mass deviation due to the 3‐D shape of the flies. Attention was paid to neutral lipids and other compounds including the male anti‐attractant 11‐cis‐vaccenyl acetate for which the expected distribution with high concentration on the tip of the male abdomen was confirmed. The red and blue mass shift (PlusMinus1 colour scale) was observed associated with mass deviation predominantly between ±0.2 and 0.3 Da. We use in‐house developed software for mass recalibration, to eliminate the mass deviation effects and help with the detection of low‐intensity mass signals. Copyright © 2014 John Wiley & Sons, Ltd.